2021
DOI: 10.3390/nano11081875
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conductive Networks from Hybrids of Carbon Nanotubes and Graphene Created by Laser Radiation

Abstract: A technology for the formation of electrically conductive nanostructures from single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), and their hybrids with reduced graphene oxide (rGO) on Si substrate has been developed. Under the action of single pulses of laser irradiation, nanowelding of SWCNT and MWCNT nanotubes with graphene sheets was obtained. Dependences of electromagnetic wave absorption by films of short and long nanotubes with subnanometer and nanometer diameters on wavelengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…To analyze the quality and durability of the laser welds formed using these solders, their microstructure must be investigated, and for solders containing SWCNT, the structure at the nanoscale must be analyzed. It has previously been shown that laser irradiation of nanotubes leads to the binding of carbon nanotubes [ 44 ]. Moreover, a laser-induced SWCNT framework structure formation in an albumin- and chitosan-based biopolymer matrix is possible [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the quality and durability of the laser welds formed using these solders, their microstructure must be investigated, and for solders containing SWCNT, the structure at the nanoscale must be analyzed. It has previously been shown that laser irradiation of nanotubes leads to the binding of carbon nanotubes [ 44 ]. Moreover, a laser-induced SWCNT framework structure formation in an albumin- and chitosan-based biopolymer matrix is possible [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The observed increase in electrical conductivity of the CNT/EP coating is due to a well-dispersed CNT into the epoxy matrix as shown in Figure 3 c. The effectiveness of electron transfer between the CNTs is very highly dependent on these CNTs’ spacing distance. CNT/EP Coating does not reach the improved percolation network formation of multi-wall carbon nanotubes but exhibits excellent electrical conductivity [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…After complete polymerization, the resulting nanocomposite was subjected to laser structuring [ 46 , 47 ]. It was treated with laser radiation to reduce the resistivity values, form welded joints between nanotubes, and form a structured MWCNT conductive network inside the nanocomposite [ 48 , 49 , 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Such methods are based on the mechanisms of action of concentrated energy, based on the latest advances in laser technology and precision mechanics. The use of the laser forming method proposed in this research makes it possible to further improve the electrical and mechanical characteristics [ 47 , 50 ]. The parameters of the laser irradiation were selected experimentally so as to prevent the combustion of the silicone.…”
Section: Methodsmentioning
confidence: 99%